Effect of Calcium‑Vitamin D Co‑Supplementation on Insulin, Insulin Sensitivity, and Glycemia: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Asbaghi, Omid; Khosroshahi, Mohammad Zeinali; Kashkooli, Sara; Abbasnezhad, Amir (Hormone and Metabolic Research, 2019)
We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the effect of calcium-vitamin D co‑supplementation on insulin, insulin sensitivity, and glycemia. A systematic search was carried out in Web of Science, PubMed, EMBASE, Scopus, and Cochrane library without any language and time restriction up to 12 August 2018, to retrieve the RCTs, which examined the effect of calcium and vitamin D co-supplementation on fasting blood glucose (FBG), insulin, HOMA-B, HOMA-IR, and QUICKI. Meta-analyses were carried out using a random effects model, and I2 indexes were used to evaluate the heterogeneity. Search yielded 2225 publications. Twelve RCTs with 4395 patients were eligible. Results demonstrated that calcium and vitamin D co‑supplementation had significantly reducing effects on FBG, HOMA-IR and circulating levels of insulin. As the subgroup analysis demonstrated, short-term (≤12 weeks) calcium and vitamin D co‑supplementation had a significant reducing effect on FBG. However, beneficial effects of calcium and vitamin D co‑supplementation on circulating level of insulin and HOMA-IR were seen in both short-term and long-term (>12 weeks) supplementations. Furthermore, we found that high doses of vitamin D and calcium co-supplementation (vitamin D≥2000 mg/day and calcium≥1000 mg/day) had significantly reducing effects on FBG, HOMA-IR and insulin. Present meta-analysis indicated the beneficial effects of high-dose and short-term combined vitamin D and calcium supplementation on insulin, insulin resistance and glycemia; however, further large-scale RCTs with adequate and multiple dosing schedules are needed.
Keywords: vitamin D; calcium; glucose; insulin; systematic review; meta-analysis